ANALYSIS OF ACTIVE LAYER THICKNESS ON THIN LAYER SOLAR CELL PERFORMANCE - Soni Prayogi; Darminto Darminto (Department of Physics, Maulana Malik Ibrahim State Islamic University of Malang, 2023)
The main objective of this research is to fabricate double-layer hydrogenated amorphous silicon (a-Si:H) using a PECVD by varying the thickness of the active layer. To obtain the thickness of the double active layer, dilution of silane plasma is carried out by hydrogen, with a ratio of hydrogen and silane, R=H2/SiH4 varies, and the deposition time of the active layer, while the n-type and n-type extrinsic layers are fixed for each -each sample. Then on the sample, there is a metal coating on the back which acts as an electrical contact and light reflector. Additionally, each sample was examined or searched for with a sun simulator and sunlight for physical properties, such as thickness morphology, optical properties, such as bandgap, electrical properties, such as electrical conductivity, and I-V characterization of a-Si: H double active layer solar cells. Based on the I-V characterization of the a-Si: H double active layer solar cells that were found in this work, a satisfactory conversion efficiency (8.86%) was found, although the Field Factor of the active layer was still low. While the intrinsic photo response reached 105